The Influence of Perceptions of Religiusity, Perceptions of Ease To Use And Perceptions of Benefits of IAIN Metro Students On Purchase Decisions Using Shopee Paylater Credit - Chaerani, Cahya; Umpusinga, Hasrun Afandi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
The purpose of this research is to determine the influence of perceived religiosity, perceived convenience and perceived benefits of IAIN Metro students on purchasing decisions using Shopee Paylater credit. This research uses quantitative methods with descriptive statistics and primary data sources by distributing questionnaires using a Likert scale. The population of this research is active even semester students at IAIN Metro for the 2022-2023 academic year. The sample in this study was 98 respondents. The data that has been obtained is then processed using the SPPS version 25 application. The results of this research in the t test, the calculated value of the Perception of Religiosity variable is -1,500 ≤ 1,661, meaning that there is no influence of Perception of Religiosity on Purchasing Decisions using Shopee Paylater. The t-count value for the Perception of Ease variable is 3,157 ≥ 1,661, meaning that there is an influence of Perception of Ease on Purchasing Decisions using Shopee Paylater. The calculated value for the Perception of Benefits variable is 6,584 ≥ 1,661, meaning that there is an influence of Perception of Benefits on Purchasing Decisions using Shopee Paylater. In the F test, the results obtained were that the value of Fcount > Ftable, 40,597 > 2,703, meaning that there was a significant simultaneous influence between the variables Perception of Religiosity, Perception of Convenience and Perception of Benefits on Purchasing Decisions using Shopee Paylater. Then the R2 test obtained a result of 0,550 or 55%.